Writing History, Shaping Images in Later Roman Empire - Milinović, Dino (Array, 2012)
The absence of Christian themes and symbols on Constantine's triumphal arch in Rome has often been understood as a proof of Constantine's phony conversion to Christianity. However, if we look closer at the iconography of imperial art throughout the 4th century, we shall discover that it rarely puts an emphasis on religious convictions of the ruler.